Boundary values for an eigenvalue problem with a singular potential - Tuz, Munevver (My University, 2017)
In this paper we consider the inverse spectral problem on the interval [0,1]. Thisdetermines the three-dimensional Schrödinger equation with from singularsymmetric potential. We show that the two spectrums uniquely identify thepotential function ??(??) in a single Sturm-Liouville equation, and we obtain newKeywords: evidence for the difference in the ??(??) ? ??(???) of the Hochstadt theorem.
Keywords: Fizik; Uygulamalı; Matematik